Reactivation of cocaine contextual memory engages mechanistic target of rapamycin/S6 kinase 1 signaling - Shi, Xiangdang; von Weltin, Eva; Fitzsimmons, Emma; Do, Chau; Caban Rivera, Carolina; Chen, Chongguang; Liu-Chen, Lee-Yuan; Unterwald, Ellen M. (Frontiers in Pharmacology, 2022)
Mechanistic target of rapamycin (mTOR)C1 and its downstream effectors have been implicated in synaptic plasticity and memory. Our prior work demonstrated that reactivation of cocaine memory engages a signaling pathway consisting of Akt, glycogen synthase kinase-3β (GSK3β), and mTORC1. The present study sought to identify other components of mTORC1 signaling involved in the reconsolidation of cocaine contextual memory, including eukaryotic translation initiation factor 4E (eIF4E)-eIF4G interactions, p70 S6 kinase polypeptide 1 (p70S6K, S6K1) activity, and activity-regulated cytoskeleton (Arc) expression. Cocaine contextual memory was established in adult CD-1 mice using conditioned place preference. After cocaine place preference was established, mice were briefly re-exposed to the cocaine-paired context to reactivate the cocaine memory and brains examined. Western blot analysis showed that phosphorylation of the mTORC1 target, p70S6K, in nucleus accumbens and hippocampus was enhanced 60 minutes following reactivation of cocaine memories. Inhibition of mTORC1 with systemic administration of rapamycin or inhibition of p70S6K with systemic PF-4708671 after reactivation of cocaine contextual memory abolished the established cocaine place preference. Immunoprecipitation assays showed that reactivation of cocaine memory did not affect eIF4E– eIF4G interactions in nucleus accumbens or hippocampus. Levels of Arc mRNA were significantly elevated 60 and 120 minutes after cocaine memory reactivation and returned to baseline 24 hours later. These findings demonstrate that mTORC1 and p70S6K are required for reconsolidation of cocaine contextual memory.